HAK KONSTITUSIONAL PENGUSULAN PASANGAN CALON PRESIDEN DAN WAKIL PRESIDEN DALAM SISTEM PEMILIHAN UMUM DI INDONESIA - Irwansyah (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2018)
Political parties in the constitution of the Republic of Indonesia and the law have constitutionalrights to propose candidates for President and Deputy President. The current electoral systemrequires that before nominating the President and Vice President, political parties must have 20percent of the vote in the legislature / DPR or obtain 25 percent of the national legitimate votes inthe previous general election. With the implementation of this system, not all political parties canpropose candidates for President and Vice President candidates. Then what is the fate of the partythat does not achieve this provision even the new party which is also the first time participating inthe general election. With the application of the nomination threshold in the electoral system inIndonesia, it will certainly restrict or limit the constitutional rights of political parties that do not meet the desired conditions of the threshold